Madrasah Vision Management Strategy in Realizing Superior Educational Quality - Dewi, Annisa Tri Ananda; Uryatul Hikmah; Ida Kusumawati; Muthi'ah Rahman; Umar Manshur (Yayasan Avicenna, 2026)
This study aims to analyze the strategy of managing the madrasah vision in realizing superior educational quality in Islamic Junior High Schools (MTs), including participatory vision formulation, socialization and internalization strategies, implementation in learning, programs, and madrasah culture, as well as evaluation and efforts to strengthen the implementation of the vision. The study used a qualitative approach with a case study design, collecting data through in-depth interviews with the madrasah principal, teachers, and students, as well as field observations of learning activities and madrasah culture, then analyzed interactively using the Miles and Huberman model. The results of the study indicate that the madrasah vision is formulated in a participatory manner so as to foster a sense of ownership and shared commitment; socialization and internalization are carried out continuously through formal forums, leadership role models, habits, and visual media so that the vision is realized in behavior and work culture; implementation of the vision is reflected in learning that integrates Islamic values, programs, and madrasah culture that supports character building and student achievement; evaluation is carried out systematically through academic supervision, evaluation meetings, and teacher performance assessments despite facing challenges such as differences in teacher understanding, limited facilities, and administrative burdens. The implications of the research show that strategic and sustainable vision management plays an important role in improving the quality of Islamic education and can be a practical reference for madrasas in developing educational management that is oriented towards academic excellence while strengthening Islamic values.